2021
DOI: 10.5114/wiitm.2021.107765
|View full text |Cite
|
Sign up to set email alerts
|

3D printing in the preoperative planning and endovascular treatment of splenic artery aneurysm. Own clinical experience and literature review.

Abstract: Splenic artery aneurysms (SAAs) are the most common visceral aneurysms. Endovascular treatment of SAAs is increasingly used. Appropriate preoperative imaging of aneurysms is crucial to treatment planning. The case of a patient with accidentally detected SAA on angio-CT examination was the basis for implementation of 3D printing to prepare an artery model. The 3D model made it easier to qualify for endovascular treatment of the SAA and helped to visualize its morphology. An excellent treatment effect was achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…For better preparation for the procedure, especially in terms of narrow iliac vessels, 3D printing devices can be used [ 20 ]. 3D printing is also efficient in detection of splanchnic artery aneurysms, which is a serious diagnostic problem in patients [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For better preparation for the procedure, especially in terms of narrow iliac vessels, 3D printing devices can be used [ 20 ]. 3D printing is also efficient in detection of splanchnic artery aneurysms, which is a serious diagnostic problem in patients [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our cases, we confirmed that more accurate visualization and analysis of vascular anatomy could assist operators in attempting minimally invasive treatment with good results. [24,25]…”
Section: Discussionmentioning
confidence: 99%
“…In our cases, we confirmed that more accurate visualization and analysis of vascular anatomy could assist operators in attempting minimally invasive treatment with good results. [24,25] 5. Conclusions 3D printing is an accessible and easy to implement method that could be widely used in treating VAAs.…”
Section: Discussionmentioning
confidence: 99%